Utilization of FucoPol for commercial inocula immobilization for bioremediation applications - Lourenço, Inês Alexandra Mariano (2021)
The purpose of this thesis was to produce FucoPol based structures and study their stability, under several conditions, in order to determine whether these structures could be applicable for bioremediation applications. For the first time, an attempt to immobilize cells in these structures matrices was also successfully performed. In this work FucoPol was produced. This exopolysaccharide were synthesized by the bacterium Enterobacter A47 and produced, using glycerol as the carbon source, in a fed-batch cultivation process. FucoPol is composed of fucose, glucose, galactose and glucuronic acid, and also contains acyl groups. The recently demonstrated gel-forming capacity of FucoPol was applied to the production of FucoPol hydrogels, films and beads. The work focused on FucoPol hydrogel structures, as they better fit the desired parameters for bioremediation applications. The stability studies revealed that FucoPol hydrogels were very stable and resistant in aqueous media (deionized water and NaCl 0.9% (w/v) aqueous solution) and under the effect of Na+ and K+ ions. The pH effect on these gels is not fully understood, but it appears that FucoPol hydrogels are more stable at more low and intermediate pH ranges (~3.5 – 7.0). FucoPol gels also revealed to be quite stable and resistant in agitation conditions, lasting between 10 to 13 weeks in these conditions. It was also reported that FucoPol hydrogels destabilized, and rapidly disintegrated in the presence of phosphate ion (PO43-), similar to that observed in Ca-alginate hydrogels. The preferential range of phosphate ion concentration, in which FucoPol hydrogels can be applied, it was also determined in [0.01; 0.4] ([PO43-] gL-1), where the hydrogel structures could last for about 1 to 9 weeks. Immobilization of inocula (P. chlororaphis and Biotask commercial inocula) in FucoPol hydrogels was very successful in the conditions presented in this work, with cellular growth being recorded in media that only contained FucoPol gel with immobilized cells. Despite these results, immobilization method should be optimized in future work in order to obtain greater cellular growth and a slower degradation of the FucoPol matrices. FucoPol hydrogels were characterized in terms of physical appearance, mechanical and morphologic properties. Inoculated hydrogels presented some differences from the non-inoculated ones. The mechanical properties of FucoPol hydrogels in general revealed relatively weak properties, but FucoPol based hydrogels presented improved mechanical properties compared with inoculated hydrogels. All the structures revealed an elastic behavior, evidenced by their high springiness. SEM images demonstrated that the three FucoPol hydrogel structures in study have different morphology, with non-inoculated FucoPol gels presenting a matrix with the smallest pores, which is in accordance with the observed differences in physical appearance of these structures. Since FucoPol hydrogels produced are non-cytotoxic, biodegradables and quite stable and resistant under several conditions, combined with the fact that cell immobilization in the gel matrix is feasible without affecting the cell viability, these structures proved to have the potential to be implemented in bioremediation applications, when a proper optimization of the final product will be achieved.